(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
Financial reporting mostly depends on the micro and macro environment. The emphasis is primarily on the institutional environment with specific differences between countries. Namely, that is one of the facts contributing to the detected gap in the implementation of financial reporting standards. From the accounting point of view the detected gap becomes more emphasised as certain national economies do not develop equally. On the other hand some authors claim in their research that implementation of standards in financial reporting has an impact on the increase of competitiveness for equal participation on the global financial capital market and they are of opinion that the implementation of International Accounting Standards and International Financial Reporting Standards is necessary for transparency and balanced presentation of balance sheet items. This paper considers the selected external factors (or environmental factors) that have impact on the diversity of financial reporting practices. The main purpose of this paper is to investigate the impact that selected external factors have on financial reporting systems. From methodological point of view, dependent and independent variables have been taken into consideration, where the results of comparative analysis show significant relation between external factors and financial reporting. Keywords: Financial reporting system, political system, economic system, inflation, accounting profession, taxation system